The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c7sc04482h
|View full text |Cite
|
Sign up to set email alerts
|

Slow magnetic relaxation in octahedral low-spin Ni(iii) complexes

Abstract: Low-spin (S = 1/2) Ni(iii) cyclam complex salts can show SMM-type properties depending on the axial ligand donor atom identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 48 publications
1
57
1
Order By: Relevance
“…Also staying within the intramolecular context, QTM cannot fully account for such a situation either. Indeed, low out-of-phase signals can still be the case even under dc magnetic fields aimed at suppressing QTM [54][55][56][57][58].…”
Section: Methodsmentioning
confidence: 99%
“…Also staying within the intramolecular context, QTM cannot fully account for such a situation either. Indeed, low out-of-phase signals can still be the case even under dc magnetic fields aimed at suppressing QTM [54][55][56][57][58].…”
Section: Methodsmentioning
confidence: 99%
“…For 1 the axial type spectrum spectrum is partially, but clearly resolved with spectroscopic splitting factors gꓕ = 2.06, g‖ = 2.28 and parallel hyperfine splitting parameter A‖ = 175 G, resulting from the interaction of the unpaired electron of Cu(II) with the spin of copper nucleus I = 3/2. It is identical for both natural isotopes of 63 Cu and 65 Cu, so eight hyperfine levels can be expected with four allowed transitions: MS=±1 and MI= 0 (Figure S19). 110 The axial EPR spectrum of compound 2 exhibits similar values of spectroscopic splitting parameters gꓕ = 2.06 and g‖ = 2.25 but with no hyperfine structure.…”
Section: Cw-epr and Pulsed Epr Studiesmentioning
confidence: 97%
“…At the same time Titiš and co-workers 64 reported the first example of a mononuclear d 8 hexacoordinate Ni(II) complex [Ni(pydc)(pydm)] (pydc = pyridine-2,6-dicarboxylate, pydm = 2,6-bis(hydroxymethyl) pyridine), demonstrating that low coordination number geometries are not a prerequisite for SIM behavior. Bhowmick et al 65 reported first example of SIM behavior in d 7 Ni(III; S = ½) complexes. Cui 66 introduced a new approach, where slow magnetic relaxation originates from the low spin state of d 7 Co(II; S = ½) ions.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 16 Diamagnetic dilution is achieved by taking a magnetic molecule and either (1) dissolving it into an organic solvent or matrix (as was done for Mn 12 O 12 ), 17 , 18 or (2) cocrystallization with a structurally analogous, closed-shell species. For example, mononuclear M 2+ complexes can be diluted with Zn 2+ 19 or low-spin Ni 2+ analogues 20 ; M 3+ species can be diluted with low-spin Co 3+ , 21 Y 3+ , 22 , 23 or Ga 3+ 24 ; and M 4+ species can be diluted with Ti 4+ . 25 In these dilute systems, wherein the size advantage of high-density molecular information storage is lost, magnetic relaxation is often slowed by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%